Assembly of phase transferred nickel nanoparticles at air-water interface using Langmuir-Blodgett technique - Bala, Tanushree; Joshi, Bhagyashree; Iyer, Neelima; Sastry, Murali; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2006)
Development of simple and efficient protocol for the synthesis of Ni nanoparticles in aqueous media and their subsequent phase transfer to organic media is reported. The synthesis of nickel nanoparticles in aqueous medium is accomplished by reducing the nickel nitrate with sodium borohydricle in presence of oleic acid. It results in the formation of nickel nanoparticles capped with oleic acid. The pristine oleic acid capped nickel nanoparticles were then phase transferred to nonpolar solvents such as toluene using stearic acid. The phase transfer was effective probably due to the space exchange between the oleic acid moiety and stearic acid molecules. The hydrophobized Ni thus obtained was organized at the air-water interface and it was observed that by controlling the pressure and concentration of hydrophobized Ni nanoparticles at air-water interface, linear ribbon like assemblies could be obtained. The organization process was followed by surface pressure-area isotherm measurement and Brewster Angle Microscopy.
Keywords: assembly; Langmuir-Blodgett technique; Ni nanoparticles; Phase transfer

Acute and subacute toxicity studies of chitosan reduced gold nanoparticles: a novel carrier for therapeutic agents - Pokharkar, Varsha; Dhar, Sheetal; Bhumkar, Devika; Mali, Vishal; Bodhankar, Subhash L.; Bhagavatula L. V. Prasad (Journal of Biomedical Nanotechnology, 2009)
The objective of the present study was to evaluate the oral toxicity of chitosan reduced gold nanoparticles so as to demonstrate its applicability for drug delivery application. Acute oral toxicity studies in female rats documented no deaths or treatment related complications. The LD(50) value of gold nanoparticles was found to be greater than 2000 mg/kg. In case of sub-acute oral toxicity studies, gold nanoparticles were administered orally to male and female rats for a period of 28-days. At the end of study blood samples were collected for haematology and biochemical analysis. For histopathological analysis, organs of animals were weighed and processed for examination. All animals survived the duration of the study, with no significant changes in clinical signs, body weight, food consumption, hematological parameters, organ weights and histopathological findings. These studies establish that chitosan reduced gold nanoparticles produced no treatment related toxicity in rats following oral administration, thus can be exploited for potential therapeutic applications.
Keywords: Acute Toxicity; Chitosan; gold nanoparticles; Sub-Acute Toxicity; Wistar Rats

Access to harmonine, a chemical weapon of ladybird beetles - Philkhana, Satish Chandra; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Reddy, D. Srinivasa (RSC Advances, 2014)
The synthesis of harmonine, a defense alkaloid from the harlequin ladybird is reported by three different routes. The preparation of several new analogs with the same molecular weight and the decoration of gold nanoparticles with harmonines are also part of the present communication.

Accelerated in vitro model for occlusion of biliary stents: investigating the role played by dietary fibre - Surwase, Sachin; Balakrishnan, Harishankar; Acharya, Subrat K.; Makharia, Govind K.; Kumaraswamy, Guruswamy; Bhagavatula L. V. Prasad (BMJ Innovations, 2018)
ackground To develop a new accelerated in vitro model that has implications for investigating the mechanism of biliary stent occlusion and help in the development of new materials that can alleviate this problem. Methods We employ a combination of reconstituted animal bile, bacteria and cellulose fibres optimised to reproducibly generate accelerated occlusion of stents, and produce occlusions that closely mimic those found in clinical studies. Results Our model affords repeatable, highly accelerated occlusion (within 2–3 days, compared with between about a week to 2 months in previous models). Our results highlight the role of dietary fibre in blockage of stents and demonstrate their importance in the onset of occlusion. Conclusions This accelerated model may have implications for developing biliary stents with enhanced patency.